2018
DOI: 10.1016/j.molimm.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression of DEC205 in the cDC1 and cDC2 subsets of porcine dendritic cells from spleen, tonsil, and submaxillary and mesenteric lymph nodes

Abstract: Conventional dendritic cells (cDCs) are divided into the following different subtypes: cDC1, which promotes a Th1 response, and cDC2, which stimulates a Th2 and Th17 response. These cells have not been characterized in porcine lymphoid tissues. DEC205 is a receptor that increases antigen presentation and allows DCs to cross-present antigens. The objectives of this work were to characterize cDCs subsets in the tonsil, submaxillary and mesenteric lymph nodes and spleen lymphoid tissues and to determine their exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…The cDC1-like cell population was identified by the high expression of MHC-II, the low/neg expression of CD172a, negative expression of CD4, CD14, and CD163 and high expression of CADM1 as described in porcine skin ( 8 ), lung ( 24 ), and blood ( 21 , 22 ). This phenotype was also described by Parra-Sanchez et al ( 25 ) in porcine tonsils. High levels of FLT3 and XCR1 mRNA expression confirmed the definition of this subset and orthology across species ( 35 , 42 ).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The cDC1-like cell population was identified by the high expression of MHC-II, the low/neg expression of CD172a, negative expression of CD4, CD14, and CD163 and high expression of CADM1 as described in porcine skin ( 8 ), lung ( 24 ), and blood ( 21 , 22 ). This phenotype was also described by Parra-Sanchez et al ( 25 ) in porcine tonsils. High levels of FLT3 and XCR1 mRNA expression confirmed the definition of this subset and orthology across species ( 35 , 42 ).…”
Section: Discussionsupporting
confidence: 80%
“…A key aim of this study was to align the identified myeloid cell populations with their human and mice counterparts and to correlate them with similar populations in porcine skin ( 7 , 8 ), lungs ( 24 ) blood ( 21 , 22 ), and lymphoid tissue, including tonsil ( 25 ). However, not all proteins can be assessed by flow cytometry in pigs, due to lack of suitable antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations